Classroom Management: the Impact of Transformational Leadership of Homeroom Teachers to the Effectiveness of Class Management in High Schools - Purwandoko, Edi; Burmansah; Poniman; Priono; Tri Anggraini (Journal of Education, Religious, and Instructions (JoERI), 2023)
This study aims to investigate the contribution of the homeroom teacher's Transformational leadership style to the effectiveness of classroom management in Senior High Schools in Bandar Lampung City. Transformational leadership emphasizes adjusting the homeroom teacher's leadership style according to the needs of students and different classroom situations. This study used a quantitative method involving homeroom teachers and students from various high schools in Bandar Lampung City as the research sample. Data was collected through questionnaires and analyzed using appropriate statistical techniques. The results showed that the homeroom teacher's Transformational leadership style significantly influenced the effectiveness of classroom management in Senior High School Bandar Lampung City. The Transformational leadership style improves classroom discipline, student participation, quality of interaction between students and teachers, and student academic achievement. The implication of this research is the importance of developing Transformational leadership skills for homeroom teachers at Senior High School Bandar Lampung City, as well as assisting schools in developing more effective classroom management strategies to improve the quality of education.